2009
DOI: 10.1371/journal.pone.0005190
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Cholera Toxin Induces Th17-Dominated T-Cell Response to Bystander Antigens

Abstract: Cholera toxin (CT) is a potent vaccine adjuvant, which promotes mucosal immunity to protein antigen given by nasal route. It has been suggested that CT promotes T helper type 2 (Th2) response and suppresses Th1 response. We here report the induction of Th17-dominated responses in mice by intranasal delivery of CT. This dramatic Th17-driving effect of CT, which was dependent on the B subunit, was observed even in Th1 or Th2-favored conditions of respiratory virus infection. These dominating Th17 responses resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 44 publications
8
63
2
1
Order By: Relevance
“…Our experiments are in agreement with a Th1 cytokine response following skin immunization [12,13] IL-17 expression by CD4 1 T cells was also observed following skin immunization with CT as has been reported using other strategies of immunization in the skin [13,14]. Recently, a dominant Th17 response was reported following intranasal immunization with OVA together with either CT or CTB [19]. In our study, the IL-17 production by CD4 1 T cells can be explained by the high expression levels of TGF-b that was observed in the Langerin 1 DCs that are present in the dermis of mice that were inoculated with CT in the ear in addition to the presence of IL-6 expressed by dermal cells (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our experiments are in agreement with a Th1 cytokine response following skin immunization [12,13] IL-17 expression by CD4 1 T cells was also observed following skin immunization with CT as has been reported using other strategies of immunization in the skin [13,14]. Recently, a dominant Th17 response was reported following intranasal immunization with OVA together with either CT or CTB [19]. In our study, the IL-17 production by CD4 1 T cells can be explained by the high expression levels of TGF-b that was observed in the Langerin 1 DCs that are present in the dermis of mice that were inoculated with CT in the ear in addition to the presence of IL-6 expressed by dermal cells (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 91%
“…When administered in the mucosa, CT can elicit a Th2-type response that is based on the production of IL-4, IL-5 and IL-10 but virtually no IFN-g [16,17]. However, a mixed Th1/Th2 response that produces both IFN-g and IL-4 has also been observed [18], and the administration of ovalbumin (OVA) in combination with CT elicits a dominant Th17 response following intranasal immunization [19]. This dominance of IL-17 was also observed in response to the CT b subunit (CTB).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent report observed that CT is able to generate Th17 cells in an IL-6-dependent manner (11), and vaccines containing CT or Escherichia coli heat-labile toxin also induced IL-17 (36)(37)(38)(39), but the mechanisms involved and the role of IL-17 in mediating adjuvant effects (i.e., antibody responses and protection against infection) were not explored. In addition, our data show that a natural biological molecule such as CT induces DCs to secrete a complex mixture of products that are required to act in combination to determine T-cell fate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In light of their important role in mucosal immunity, we hypothesized that Th17 cells may contribute to the mucosal adjuvant effects of CT. Indeed, a recent report identified the ability of CT to induce Th17 cells (11), although the role of these cells in mediating the adjuvant effects of CT remains unresolved.…”
mentioning
confidence: 99%
“…33 Therefore high doses of antigen and multiple immunizations have been required for the successful induction of local antibody responses by vaginal immunization alone. 34 Alternatively, mucosal adjuvants may be considered for the successful induction of immunity via the vaginal route, although many candidate mucosal adjuvants such as the non-toxic cholera toxin B subunit (CTB), 35 or CpG oligodesoxynucleotides 36,37 induce proinflammatory responses, which has raised concerns because of the potential risks of local inflammation resulting in increased susceptibility to HIV-1 infection. A promising immunization strategy is therefore to combine an adjuvanted systemic, intranasal or sublingual prime immunization inducing potent primary responses with a vaginal mucosal boost immunization to focus the initial immune response toward the genital mucosa.…”
Section: The Need For Better Mucosal Adjuvantsmentioning
confidence: 99%